Components Acquaintance of Fuel Oil System Using Virtual Reality Application - Hari Prastowo; Trika Pitana; Gusti Ngurah Putu Wibhu Ary Martha (Institut Teknologi Sepuluh Nopember, 2020)
Indonesia is known as the biggest archipelagic nation on the planet and is between two significant seas. In a roundabout way, Indonesia has tremendous regional water when contrasted and the land territory itself. With this, obviously, it tends to be said that Indonesia has colossal potential in the oceanic area, particularly since the Indonesian sea domain has consistently been a worldwide transportation path. This potential should be used ideally by this country, considering the mechanical advancement in Indonesia itself can be supposed to be very quick. Innovation that is utilized carefully and applied to the sea world can give Indonesia benefits for a few areas, for example, the economy, industry, and even schooling. Innovation that can be used in the oceanic world, particularly in the field of transportation is PC illustrations innovation, which in its application can be utilized during the time spent to plan, fix and support, reproductions and preparing for training and others with the 3D display. Virtual Reality (VR) is a counterfeit world or can be said as a computerized world where everything in there is the consequence of representation made utilizing 3D innovation from the PC. Virtual Reality permits us to cooperate and encounter encounters that are practically like this present reality. The reason for this exploration or the last task is to use innovation that is growing quickly well in the learning cycle in the oceanic world. With Virtual Reality, it is conceivable to make new learning strategies for training, particularly in the presentation of segments of the fuel oil framework on the ship. Because of a few restrictions confronted when mentioning direct objective facts to the ship, including authorization or admittance to enter the ship, time is restricted. Along these lines, it is normal that utilizing Virtual Reality can help the learning cycle for training by making an application that can be utilized in perceiving and understanding the segments of the fuel oil framework on a ship.